The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/pan.13830
|View full text |Cite
|
Sign up to set email alerts
|

A prospective observational study of postoperative follow‐ups and outcomes at a nonprofit, internationally supported pediatric surgery center in Guatemala

Abstract: Background: Global surgical access is unequally distributed, with the greatest surgical burden in low-and middle-income countries, where surgical care is often supplemented by nongovernmental organizations. Quality data from organizations providing this care are rarely collected or reported. The Moore Pediatric Surgery Center in Guatemala City, Guatemala, is unique in that it offers a permanently staffed, freestanding pediatric surgical center. Visiting surgical teams supplement the local permanent staff by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…a total of 15 to 20 US surgical teams provide care annually. Visiting groups bring a multidisciplinary cohort of providers including surgeons, anesthesiologists, nurse anesthetists, operating room nurses, PACU nurses, and ancillary health care staff 22 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…a total of 15 to 20 US surgical teams provide care annually. Visiting groups bring a multidisciplinary cohort of providers including surgeons, anesthesiologists, nurse anesthetists, operating room nurses, PACU nurses, and ancillary health care staff 22 …”
mentioning
confidence: 99%
“…Visiting groups bring a multidisciplinary cohort of providers including surgeons, anesthesiologists, nurse anesthetists, operating room nurses, PACU nurses, and ancillary health care staff. 22 The center performs outpatient surgical procedures and utilizes a standard postoperative follow-up plan. Pediatric Otolaryngology-Head and Neck procedures comprise the majority of surgeries.…”
mentioning
confidence: 99%
“…However, this study also introduces a potential issue with such mission trips: Only 29% of patients were reachable for follow-up. 7 It is evident that such structural barriers to care among rural and low-income communities must be addressed in the development of orthopaedic missions. Addressing this disparity in health care is a great first step, but studies have shown that mission trips may have some serious downfalls.…”
mentioning
confidence: 99%